Navigating Security Models and Emerging Cyber Security Threats: An In-Depth Exploration - Chowdary Velevela, Raghu Ram (Journal of Information Security System and Cyber Criminology Research, 2024)
Cybersecurity often overlaps with information security, emphasizing the critical role of human behavior and considering individuals as potential targets for cyber-attacks. This overlap highlights the importance of understanding how intentional and unintentional human actions can create vulnerabilities in information systems. This paper delves into the ethical implications of cyber security, examining the moral responsibilities of individuals and organizations in protecting sensitive data. It reviews various frameworks and models developed to address these ethical concerns, analyzing their effectiveness and areas for improvement. Additionally, the paper explores past techniques employed to mitigate cyber-threats, evaluating their successes and limitations. By doing so, it identifies gaps in current practices. The paper seeks to enhance understanding of the current cyber-security landscape and offer insights into how these models can be improved to better address evolving threats. It provides recommendations for future research, aiming to enhance the resilience of cyber security measures and promote a more secure digital environment.